Dandy Paris and Patroclus the Vulgar Gent: Comic Pain and Masculinity in Trojan War Epic Burlesques of Nineteenth-Century London Stage - Ala-Lehtimäki, Henna (Springer Nature, 2026)
The nineteenth-century burlesques drew inspiration from various sources, including ancient epic and mythology, thus using the classics as a background for contemporary discussions. In this paper, the portrayal of comic pain and masculinity in two epic burlesques of the Trojan War—Thomas Dibdin’s Melodrame Mad! or, the Siege of Troy (1819) and Robert Brough’s Iliad; or, the Siege of Troy (1858)—is brought into closer analysis. Through the characters of Paris and Patroclus, the study explores how violence and comic humiliation served as means for constructing masculine ideals on stage. By parodying classical sources by transforming Homeric duels into pugilistic contests, their comic framing exposed cultural anxieties about effeminacy, social class and national identity.